Dynamics of contractile function of the left atrium in patients, suffering ischemic mitral regurgitation - S. I. Musayev; E. F. Gurbanov (Клінічна хірургія)
Objective. Estimation of mechanical function of the left atrium in patients, suffering an ischemic mitral regurgitation, using technology of the vector analysis of the endocardium movement speed.